Analysis Of Ionospheric Effects On Ground-Based Augmentation System (Gbas) At Klia, Malaysia - Zamzuri, Amira Nur’izzah (Universiti Sains Malaysia, 2021)
Instrument Landing System (ILS) is recognised by ICAO as a standard precision landing aid that provides accurate location and descent guidance for aircraft to land on the runway. An alternative to the ILS, Global Positioning System (GPS) is implemented for aircraft navigation. The current GPS navigation system cannot meet the real-time integrity monitoring required for safety needs in the aviation system. Therefore, several augmentation systems have been introduced to overcome the limitation. Global Based Augmentation System (GBAS) is one of the augmentation systems that enhanced the levels of service supporting all phases of approach, landing, departure, and surface operations. Ionospheric scintillation is the abnormality that occurs in the signal transmission during GBAS operation. It is produced by ionising radiation from the Sun and controlled by chemical interactions and transport by diffusion and neutral wind. Sufficiently intense will cause irregularities during transmission that scatter the radio waves and generate rapid fluctuations (or scintillation) in the amplitude and phase of radio signals. Data acquired from the GBAS installed at Kuala Lumpur International Airport was observed to measure the S4 values indicating the strength of amplitude scintillation. Due to insufficient data obtained, a full year of data analysis is incomplete. However, the data is enough to conduct studies on how ionospheric scintillation can affect the GBAS operation. An equinox month suspected of the ionospheric scintillation to occur was selected to ease the study. Selected data is used to observe the behaviour of the S4 values, and a comparison is made from that data. This is to analyse the effect of the scintillation on the signal transmission process and their effect on the GBAS system. There is a distinct difference in the three receivers located at GBAS in KLIA, Malaysia. It is found that the maximum S4 values and the time of its occurrence are different between the three receivers.Results show that only low ionospheric scintillation is present during the operation as the signals fluctuate when received by the GPS receiver. The highest number of PRN that experienced weak scintillation is on the 11th, 12th and 27 of September 2017, with the maximum S4 value of 0.3492, 0.3325 and 0.3387. Meanwhile, only four PRN on 6th and 13th March 2018 experienced weak scintillation with a maximum value of 0.3735 and 0.3350. The results indicate that the highest S4 values occur in the month cannot affect the GBAS system as it is not intense. There is no high scintillation event in September 2017 and March 2018 as it is during solar minimum.